PENGARUH POLA ASUH ORANG TUA TERHADAP MINAT BELAJAR SISWA KELAS V DI SD MUHAMMADIYAH 1 PANJI SITUBONDO TAHUN AJARAN 2016/2017 - Amalia Risqi Puspitaningtyas (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2016)
Parents have a very big role in children's education at home. The role of parents is the share of parents in providing good for their children for the sake of education keberprestasian undertaken. The indicator is the role of parents is the attention to the activities of children at school lessons and emphasize the importance of learning achievement. Teachers play a role of educating children so that children are ready to meet the future, but the attention of the parents or the family also has an active role in educating children and motivating learning. The problems of this research is there any Parenting Parents Influence on Students' Interest in Learning in Schools. Methods This study included descriptive research with quantitative conclusion through statistical analysis. The population in this study were all fifth grade students of SD Muhammadiyah 1 Panji Situbondo. Samples taken as many as 40 students. Based on the results of research, data analysis and hypothesis testing, it can be concluded as follows: there is significant influence between parenting parents with student interest in V in SD Muhammadiyah 1 Panji Situbondo in the academic year 2016/2017. This is evidenced from the results of the rtabel distribution of 5% or 0.05 at 0.257, then rhitung 0,363> rtabel 0,257dan Ha accepted, which means "Parenting Parents (X) significantly affects Interest in learning (Y)